Sistem Opersionl Lelang BPPKD Kabupaten Purworejo Perspektif Hukum Islam dan Hukum Positif - Fathudin Fathudin; Adi Wibowo; Hajar Mukaromah; Muhammad Mustahal; Ro’ihatul Munawaroh (JURNAL HAKAM, 2020)
At present many transactions are done by the community one of them is ba'i al-muzāyadah. BPPKAD (Finance and Regional Asset Management Agency) Purworejo Regency Practice the ba'i al-muzāyadah in selling inventory items that are not usable in equipment because they are damaged or for development, namely The sales auction with a single-cover closed bidding method, in the sense of a letter of bidding (a bid size) along with all requirement files inserted in one closed envelope. Therefore, among the bidders can not know each other's offerings from other participants. This is different from the auction system in the Fiqh rulings (Islamic law) is an auction with a method of bidding in the middle of the crowd or public and the price quote is done repeatedly to find the auction winner. Departing from the background, researchers interested in discussing the problems of the BPPKAD auction operational system (the financial and Regional Asset Management Board) of Purworejo Regency using the perspective of Islamic law. With the aim that researchers can research more in whether the auction system used by BPPKAD Purworejo District is already in accordance with Islamic law. This type of research is a type of field study, the method of collecting data by interview. There are two data sources that are primary data sources and secondary data sources while the analysis uses a qualitative approach.